2013
DOI: 10.7567/apex.6.076502
|View full text |Cite
|
Sign up to set email alerts
|

Very Thin Extreme Ultraviolet Mask Absorber Material for Extremely Fine Pitch Patterning

Abstract: In this report, we propose palladium oxide (PdO) as an absorber material for an EUV mask that can print line-and-space patterns with a half pitch down to 14 nm. In our simulations, because of its low refractive index (n = 0.8634) and high extinction coefficient (k = 0.0536), an attenuated phase shift mask with a very thin (∼20 nm) PdO absorber can provide an EUV contrast as high as 88% at a 14 nm half pitch under dipole illumination. This results in a very limited horizontal–vertical critical dimension bias (≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…As a matter of fact, the refractive index of Pd 46 is generally larger than that of PdO. 47,48 Finally, a weak signal appeared gradually at 1988 cm −1 along PdO reduction that could be assigned to ν(Pd−H). This assignment remains tentative because Pd hydrides are predominantly bridged species, and the corresponding vibrational modes appear at lower energy.…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, the refractive index of Pd 46 is generally larger than that of PdO. 47,48 Finally, a weak signal appeared gradually at 1988 cm −1 along PdO reduction that could be assigned to ν(Pd−H). This assignment remains tentative because Pd hydrides are predominantly bridged species, and the corresponding vibrational modes appear at lower energy.…”
Section: Resultsmentioning
confidence: 99%
“…10 Soon after that Obert Wood et al from Lucent reported the first experimental realization of attPSM for EUV including extensive simulation studies. 11 Since then, many different forms of attPSM for EUV including etched multilayer configurations [12][13][14] and various absorber stack configurations [15][16][17] were proposed and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, absorber materials with appropriate combinations of refractive index n and extinction k can be used to devise attenuated phase shift masks (PSM) for EUV. Both approaches have been investigated for EUV systems with an NA of 0.33, [17][18][19][20][21] including a first experimental demonstration of improved imaging performance of high k absorbers. 22 The effective thickness of EUV masks depends also on the multilayer.…”
Section: Paths Toward Mitigationmentioning
confidence: 99%